Quantifying the impacts of climate change and ecological restoration on streamflow changes based on a Budyko hydrological model in China's Loess Plateau. Issue 8 (21st August 2015) - Liang, Wei; Bai, Dan; Wang, Feiyu; Fu, Bojie; Yan, Junping; Wang, Shuai; Yang, Yuting; Long, Di; Feng, Minquan
Abstract Understanding hydrological effects of ecological restoration (ER) is fundamental to develop effective measures guiding future ER and to adapt climate change in China's Loess Plateau (LP). Streamflow (Q) is an important indicator of hydrological processes that represents the combined effects of climatic and land surface conditions. Here 14 catchments located in the LP were chosen to explore the Q response to different driving factors during the period 1961–2009 by using elasticity and decomposition methods based on the Budyko framework. Our results show that (1) annual Q exhibited a decreasing trend in all catchments (−0.30 ∼ −1.71 mm yr−2), with an average reduction of −0.87 mm yr−2. The runoff coefficients in flood season and nonflood season were both decreasing between two periods divided by the changing point in annual Q series; (2) the precipitation (P) and potential evapotranspiration (E0) elasticity of Q are 2.75 and −1.75, respectively, indicating that Q is more sensitive to changes in P than that in E0; (3) the two methods consistently demonstrated that, on average, ER (62%) contributing to Q reduction was much larger than that of climate change (38%). In addition, parameter n that entails catchment characteristics in the Budyko framework showed positive correlation with the relative area of ER measures in all catchments (eight of them are statistically significant with p < 0.05). These findings highlight the importance of ER measures on modifying the hydrological partitioning in the region. However, ER actions over the sloping parts of the landscape weakened the impact of those in channels (i.e., check‐dams) on Q, especially after the implementation of the Grain‐for‐Green project in 1999.